The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1468-3083.2006.02091.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with acne: beliefs and perceptions in a sample of secondary school Greek pupils

Abstract: Beliefs of Greek adolescents about acne were shown to be similar to those of pupils in other developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
49
6
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 21 publications
14
49
6
2
Order By: Relevance
“…This result is in accordance with the finding of a Greek study (59.2%) 16 , but it is significantly lower than in several other studies with the range from 70.0% to over 90% 9,[17][18][19][20] . We have to mention that a significantly higher acne prevalence was in Užice (73.6%) than in Belgrade (39.6%), without any reasonable explanation for this finding.…”
Section: Discussionsupporting
confidence: 94%
“…This result is in accordance with the finding of a Greek study (59.2%) 16 , but it is significantly lower than in several other studies with the range from 70.0% to over 90% 9,[17][18][19][20] . We have to mention that a significantly higher acne prevalence was in Užice (73.6%) than in Belgrade (39.6%), without any reasonable explanation for this finding.…”
Section: Discussionsupporting
confidence: 94%
“…The prevalence of self-reported acne in this study (76%) is somewhat lower than in Scottish study [8] and higher than in Greek, [9] Japanese, [10] and Chinese study. [11] Although the comparison of prevalence between different studies is in general difficult because of differences in questionnaire design, settings and the population characteristics, our study confirms that acne is common in teenagers.…”
Section: Discussioncontrasting
confidence: 82%
“…In a study from Greece, high-school students implicated diet (62.3 %), hormones (55.1 %), poor hygiene (42.4 %), stress (31.9 %), infection (14.9 %), and genetics (5.7 %) as causes for their acne [ 9 ]. Another study among acne patients visiting a community-based hospital in Saudi Arabia found that most patients believed that hormonal imbalance and dirt were the major causes of acne [ 10 ].…”
Section: Introductionmentioning
confidence: 98%